ПОДГОТОВКА ДОКТОРОВ ПЕДАГОГИЧЕСКИХ НАУК В УЧРЕЖДЕНИИ ОБРАЗОВАНИЯ «БЕЛОРУССКИЙ ГОСУДАРСТВЕННЫЙ ПЕДАГОГИЧЕСКИЙ УНИВЕРСИТЕТ ИМЕНИ МАКСИМА ТАНКА» (1991 – 2020 гг.) - Маковчик, А.В.; Шеститко, И.В. (SCIENCE and SOCIETY, 2025)
The article examines the process of training doctors of pedagogical sciences at the Maxim Tank Belarusian State Pedagogical University in the period from 1991 to 2020. The analysis of the topics and dynamics of defending 31 doctoral dissertations in various pedagogical specialties is presented. Priority areas of scientific research have been identified: methods of teaching mathematics, historical and pedagogical research, and musical and artistic personal development. The periods of activity and decline in doctoral dissertations are considered, scientific schools and their contribution to the development of pedagogical science are characterized. The work focuses on the role of the university community in shaping the scientific potential of the country and the relevance of research for further strategic planning in the field of training highly qualified teachers.
Keywords: pedagogical sciences; doctoral thesis; Belarusian State Pedagogical University; scientific schools; teaching methods; mathematical education; musical education; historical and pedagogical research